2019
DOI: 10.37358/mp.19.3.5243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Exogenous Colorants Effects on Resin Based Materials Used in Incipient Caries Lesions Therapy

Abstract: The aim of this study was to evaluate the potential of coloring of two commercial beverages: coffee and wine, and cigarette smoke, on three materials (ICON infiltration resin, MI Varnish Recaldent, and a sealant based on composite resin) currently used in incipient caries therapy. The study group included 75 extracted teeth that were divided into 3 groups corresponding to each material used. The groups were divided into 5 subgroups that corresponded to each colorant (A. red wine, B. coffee, C. cigarette smoke,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Five studies assessed the effect of cigarette smoke on resin composite (Figure 3 ) (Belli et al, 1997 ; Mathias, Costa, et al, 2010 ; Mathias et al, 2011 ; Taraboanta et al, 2019 ; Vohra et al, 2020 ). Data from four studies were pooled (Mathias, Costa, et al, 2010 ; Mathias et al, 2011 ; Taraboanta et al, 2019 ; Vohra et al, 2020 ) two of which (Mathias, Costa, et al, 2010 ; Taraboanta et al, 2019 ) had subgroups of resin composite materials, into a dataset and found evidence that cigarette smoke causes increased staining of resin composite materials when compared to a non‐smoker exposure control of (MD: 11.90; 95% CI: 11.47, 12.34; I 2 : 100%). The study not included in the meta‐analysis, Belli et al ( 1997 ), also showed evidence of an increase in staining in two resin composites tested upon exposure to cigarette smoke versus a distilled water control (Supporting Information: Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies assessed the effect of cigarette smoke on resin composite (Figure 3 ) (Belli et al, 1997 ; Mathias, Costa, et al, 2010 ; Mathias et al, 2011 ; Taraboanta et al, 2019 ; Vohra et al, 2020 ). Data from four studies were pooled (Mathias, Costa, et al, 2010 ; Mathias et al, 2011 ; Taraboanta et al, 2019 ; Vohra et al, 2020 ) two of which (Mathias, Costa, et al, 2010 ; Taraboanta et al, 2019 ) had subgroups of resin composite materials, into a dataset and found evidence that cigarette smoke causes increased staining of resin composite materials when compared to a non‐smoker exposure control of (MD: 11.90; 95% CI: 11.47, 12.34; I 2 : 100%). The study not included in the meta‐analysis, Belli et al ( 1997 ), also showed evidence of an increase in staining in two resin composites tested upon exposure to cigarette smoke versus a distilled water control (Supporting Information: Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies compared the staining effects on different types of resin composite (Alandia‐Roman et al, 2013 ; Belli et al, 1997 ; Malhotra et al, 2011 ; Mathias, Costa, et al, 2010 ; Mathias, Silva, et al, 2010 ; Taraboanta et al, 2019 ; Theobaldo et al, 2020 ; Wasilewski Mde et al, 2010 ). The data from these studies could not be pooled due to the variation of resin composite products used and differences in methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation